2011
DOI: 10.3390/rel2040485
|View full text |Cite
|
Sign up to set email alerts
|

Does Religious Involvement Generate or Inhibit Fear of Crime?

Abstract: Abstract:In victimology, fear of crime is understood as an emotional response to the perceived threat of crime. Fear of crime has been found to be affected by several variables besides local crime rates and personal experiences with victimization. This study examines the relationship between religion and fear of crime, an underexplored topic in the criminological literature. This gap is rather surprising given the central role religion has been found to play in shaping the attitudes and perceptions of congrega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 33 publications
1
9
1
Order By: Relevance
“…The lack of a direct correlation between fear of crime and religiosity is compatible with other findings (Shechory-Bitton & Silawi, 2019). However, the findings in this context are not unequivocal, as others have reported that religious faith reduces fear of crime (e.g., Matthews, Johnson, & Jenks, 2011). This must be further studied.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…The lack of a direct correlation between fear of crime and religiosity is compatible with other findings (Shechory-Bitton & Silawi, 2019). However, the findings in this context are not unequivocal, as others have reported that religious faith reduces fear of crime (e.g., Matthews, Johnson, & Jenks, 2011). This must be further studied.…”
Section: Discussioncontrasting
confidence: 55%
“…In any case, it may be assumed that religion can serve as a buffer to fear. Compatible with the findings of others (e.g., Matthews et al, 2011), religious people described their neighborhood as safer and their social relationships as stronger than did secular people, predicting lower levels of fear.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…As no one has directly examined the effect of religious involvement on gun ownership, we can only speculate on possible connections based on research on other outcomes. For example, Matthews, Johnson, and Jenks () find religious involvement related to lower levels of fear of certain types of crime. They connect higher levels of religious involvement to lower levels of fear through the lower levels of misanthropy among those who are more religiously involved.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A small number of studies have found religious involvement to be related to perceptions having to do with crime itself. For example, in a sample of residents in western Georgia (United States), Matthews, Johnson, and Jenks (Matthews et al 2011) found that attendance at religious services was negatively related to fear of property crime, suggesting that religious involvement reduces fear of victimization. In addition, several studies have examined the impact of religion upon criminal behavior, usually finding that religion variables are associated with lower criminality (Adamczyk et al 2017).…”
Section: Introductionmentioning
confidence: 99%